STRATEGIES USED BY ENGLISH TEACHER FOR STUDENTS WITH SPECIAL NEEDS - Hapitri, Resa (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
Accommodating children with special needs as much as possible in educational institutions means that some of their needs are met. It is hoped that the education they receive will allow them to broaden their horizons in life. so they can think creatively, innovatively, and productively. No one wants to be disabled or imperfect like other children. Being disabled doesn't mean they can't do anything. Thus, this research is focused on finding the strategies faced by English teachers in teaching students with special needs. The participant involved in this study is one of the English teachers in a special-needs school who has experience in teaching English. Data was collected using semi-structured interviews. The results show that the strategies used by teachers when teaching English are a student-centered approach and the use of repetition to help students remember lessons. This study found that there are three topics about strategies used by English teacher for students with special needs, which are needed to help the researcher answer the researcher's questions. The topics are: teacher understanding of special-needs students’ characteristics; teaching challenges; and teaching strategies.